Decompilation and copyright in ideas - the protection of non-literal elements of computer software and the idea/expression dichotomy - Jooste, Jacobus Petrus (Stellenbosch : Stellenbosch University, 2020)
Thesis (LLD)--Stellenbosch University, 2020.